TINGKAT PEMANFAATAN DAN FAKTOR FAKTOR YANG MEMPENGARUHI PEMAKAIAN JEMBATAN PENYEBERANGAN ORANG DI DEPAN MALL TATURA KOTA PALU - Mashuri, Mashuri; Widodo, Sigit (MEKTEK, 2012)
One cause of the disruption of traffic on urban road are pedestrian crossing the street. The bridge crossing is one of the transportation infrastructure which aims to minimize traffic discruption by pedestrian crossing. The purpose of this study was to determine the level of utilization and factors that effect the use of the pedestrian bridge in front of Mall Tatura, Palu city. The research data includes the volume of pedestrians using the bridge crossing and pedestrian volume arenot using pedestrians bridge crossing. Data was collected in the peakhours on weekdays and outside the working day. The data analysis using statistical methods includes Cronbachâ€™s Alpha Test, Relative RankIndex Test and Correlation Spearman Rank Testing. The result of this study is to found that the utilization rate of the pedestrian bridge in front of the Mall Tatura, Palu city is not very helpful.Â Factors effecting the use of pedestrian bridge in the study area includes geometric/dimensional of bridge crossing, distance to/from the bus stop, the texture of the floor, the travel time to/from the centre of activity, travel time to/from the bus stop infrastructure, and lighting on the bridge crossing.